CHEMISTRY OF TORRENT WATER IN AZAD JAMMU & KASHMIR, PAKISTAN - Mirza, M. A.; Arain, G. M.; Khuhawar, M. Y.; Arain, R. (The Nucleus, 2020)
A field study was conducted to estimate the seasonal and regional variations in physicochemical characteristics of water of the hill torrents located in Azad Jammu & Kashmir where torrent water is used for drinking purposes. Ten torrents within the populated areas were selected and analyzed for about 30 parameters, including four major and seven minor metal contents. The monitoring was carried out for summer, autumn and winter during 2004 – 2005. Total dissolved solids (TDS) were observed within 145 – 561 μg/ml and 50 % of the torrent water crossed the limit of 500 μg/ml for TDS. For lead 80 %, for cadmium 90 % and for Kjeldahl nitrogen 40 % of studied torrents indicated higher values than the permissible limits of WHO for drinking water. No significant changes were observed in torrent water quality during different seasons.